Midline Cervical Cleft: Review of an Uncommon Entity - Liana Puscas (International Journal of Pediatrics)
Introduction. Midline cervical cleft is a rare congenital malformation which nonetheless has a classic presentation. This study presents one of the largest single series of new patients with MCC and provides an exhaustive review and catalogue of publications from the international literature. Materials and Methods. Retrospective chart review performed in two academic medical centers and literature review performed with primary verification of all quoted references. Results. Ten patients with MCC were identified (8 boys and 2 girls). All patients presented with the classic findings of this congenital anomaly, and the length of the skin defect correlated with an increase in the patient’s age. Surgical excision was complete in all cases. Thorough international literature review yielded only 195 verifiable previously reported cases. Conclusions. This is one of the largest series of new patients with midline cervical cleft presented in the world literature. Although rare (with less than 200 cases published to date) this entity does have a reliable presentation that should lead to rapid and accurate diagnosis. Complete surgical excision at an early age is appropriate since the anomaly increases in length commensurate with the patient’s age.